Public investment in R&D in reaction to economic crises: A longitudinal study for OECD countries - Maikel Pellens; Bettina Peters; Martin Hud; Christian Rammer; Georg Licht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
The paper investigates the reaction of public R&D spending on economic crises. We are interested in two counteracting motives: On the one hand, public R&D spending can be seen as a means to fight the crisis, and governments may decide to increase their R&D budgets. On the other hand, a crisis reduces public income and urges governments to cut spending, which may negatively affect public R&D budgets. Using panel data from 26 OECD countries over the period 1995 to 2015, we investigate how public R&D expenditure changes over the business cycle for different types of government R&D expenditure. On average, we find evidence for a strong pro-cyclical effect on public R&D investments. But country heterogeneity matters. Whereas European innovation leaders and non-EU countries pursue a counter-cyclical strategy, innovation followers and moderate innovators behave pro-cyclical. This leads to an increasing innovation gap in Europe. Short-run and long-run financing conditions (budget surplus and government debt levels) also significantly affect public R&D spending. However, there is no evidence that economic crises systematically affect the composition of public R&D spending along different thematic areas or by beneficiaries.
urn:nbn:de:bsz:180-madoc-446032
Keywords: H54; H12; H61; 330; public R&D expenditure; economic crisis; OECD; panel data